Tiras, timbres y estereotipos: el negro Memín Pinguín y la manipulación de la cultura popular con representaciones étnicas - Katz, Marco (My University, 2007)
Memín Pinguín is the Black protagonist in a famous set of comics that first appeared in Mexico in 1945. However coincidental, the proximity of a speech by the Mexican President on 13 May 2005 and the appearance a fortnight later of five postage stamps commemorating Memín Pinguín suggests a connection between these two events. This study of the Memín Pinguín stamp controversy, connected to the presidential speech, explains how postage stamps function as a literary genre —a type of cuento corto, perhaps, among comic strips— and considers the ways in which these texts cross national, linguistic, and cultural borders, creating questions about ethnic images and who has the right to manage them.
Keywords: Memín; Vicente Fox; George Bush; borders; comics; philatelic; racism; stereotypes; postage stamps